PENGARUH MARKET ORIENTATION, ARTIFICIAL INTELLIGENCE MARKETING ADOPTION, DAN DIGITAL MARKETING CAPABILITY TERHADAP KINERJA PEMASARAN UMKM DI KOTA KENDARI - Dzulfikri Azis Muthalib (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze the effect of market orientation, artificial intelligence marketing adoption, and digital marketing capability on the marketing performance of micro, small, and medium enterprises (MSMEs) in Kendari City. This research employs a quantitative approach with a causal research design. Data were collected through a questionnaire using a five-point Likert scale from 99 MSME owners selected through purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 26. The results indicate that market orientation has a positive and significant effect on marketing performance. Artificial intelligence marketing adoption also has a positive and significant effect on marketing performance. Digital marketing capability has a positive and significant effect and demonstrates the most dominant influence among the three variables. Simultaneously, market orientation, artificial intelligence marketing adoption, and digital marketing capability significantly affect marketing performance.